NILAI MANFAAT EKONOMI AIR HUTAN LARANGAN ADAT RUMBIO - Insusanty, Enny; Ratnaningsih, Ambar Tri (Fakultas Kehutanan Universitas Lancang Kuning, 2015)
This study aims to determine the estimated economic value of water in Rumbio Forest Indigenous Prohibition for domestic use existing community around the forest. The method of data collection is done in a survey by random sampling. The economic value of water for domestic use Rp 347 871 206 per year. Willingness to pay (WTP) is Rp1.907.657.086 per year in order to obtain the consumer surplus of Rp 1,559,785,880 per year. In addition there are 13 businesses sales of water to three villages around the Rumbio forest indigenous prohibition.